齿侧间隙对齿轮机构响应频率的影响研究 - 肖回鹏; 罗欣; 徐振高 (Jixie chuandong)
In order to simulate the effects of backlash on response frequency of gear mechanism in engineering application,the multi-rigid-model of one-stage gear mechanism including backlash is established.The parameters of geartooth contact-impact force model are obtained by means of curve approximation et al.Through dynamic simulation analysis on the gear mechanism,the response frequency of gear mechanism with backlash is obtained as well as the response frequency of gear mechanism without backlash.The corresponding relationship of response frequency of gear mechanism and gear backlash is also presented.The results show that response frequency of gear mechanism will be reduced by gear backlash and multi-frequency phenomenon will occur.Based on this,the gear backlash can be rationally selected and the dynamic characteristics of the mechanism will be improved.